2015
DOI: 10.1002/ddr.21238
|View full text |Cite
|
Sign up to set email alerts
|

5‐HT2B Receptor Antagonists Reduce Nerve Injury‐Induced Tactile Allodynia and Expression of 5‐HT2B Receptors

Abstract: Preclinical Research This work was performed to assess the effects of intrathecal serotonin 2B (5-HT ) receptor antagonists in rats with neuropathic pain. With RS-127445, its effect was also determined on 5-HT receptor expression. Neuropathic pain was induced by L5/L6 spinal nerve ligation. Western blotting was used to determine 5-HT receptor expression. Dose-response curves with the 5-HT receptor antagonists 2-amino-4-(4-fluoronaphth-1-yl)-6-isopropylpyridine (RS-127445, 1-100 nmol) and 1-[(2-chloro-3,4-dimet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…Several studies have demonstrated that activation of spinal 5‐HT 1A/1B (Colpaert et al, ) and 5‐HT 5 (Avila‐Rojas et al, ) receptors reduced the behavioral or electrophysiological measures related to neuropathic pain. On the other hand, behavioral or electrophysiological studies demonstrated that the activation of the 5‐HT 2/3/4/6/7 receptor produced a pronociceptive effect (Pineda‐Farias, Velázquez‐Lagunas, Barragán‐Iglesias, Cervantes‐Durán, & Granados‐Soto, ), and these receptors are expressed in the dorsal horn of the spinal cord (Bardin, Bardin, Lavarenne, & Eschalier, ). Accordingly, we found that pretreatment with WAY‐100635 (6 μg per rat), SB‐224289 (5 μg per rat), BRL‐15572 (4 μg per rat), and SB‐699551(6 μg per rat) via intrathecal administration prevented the [6]‐gingerol‐induced antiallodynic effect in neuropathic rats.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that activation of spinal 5‐HT 1A/1B (Colpaert et al, ) and 5‐HT 5 (Avila‐Rojas et al, ) receptors reduced the behavioral or electrophysiological measures related to neuropathic pain. On the other hand, behavioral or electrophysiological studies demonstrated that the activation of the 5‐HT 2/3/4/6/7 receptor produced a pronociceptive effect (Pineda‐Farias, Velázquez‐Lagunas, Barragán‐Iglesias, Cervantes‐Durán, & Granados‐Soto, ), and these receptors are expressed in the dorsal horn of the spinal cord (Bardin, Bardin, Lavarenne, & Eschalier, ). Accordingly, we found that pretreatment with WAY‐100635 (6 μg per rat), SB‐224289 (5 μg per rat), BRL‐15572 (4 μg per rat), and SB‐699551(6 μg per rat) via intrathecal administration prevented the [6]‐gingerol‐induced antiallodynic effect in neuropathic rats.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in another study, spinal administration of RS-127445 prevented the development and maintenance of the long-lasting hyperalgesia induced by formalin injection into the rat hindpaw 24) . Furthermore, in the spinal nerve ligation model of neuropathic pain in rats, thermal or mechanical allodynia was shown to be attenuated by spinal 5HT 2B receptor inhibition induced by the 5HT 2B receptor antagonists RS-127445 25) , LY-266097 25) , and SB204741 26) . As a mechanistic perspective, Aira et al proposed convergent synaptic input from a descending serotonergic varicosity and a primary C afferent fiber onto neurons at spinal superficial dorsal horn, and that activation of postsynaptic 5HT 2B receptor at the superficial dorsal horn by increased activity of descending serotonergic pathway would lead to dorsal horn hyperexcitablity to input from primary afferent fibers in the spinal nerve ligation model of neuropathic pain 26) .…”
Section: Biological and Pharmaceutical Bulletin Advance Publicationmentioning
confidence: 97%
“…In the rat brain 5-HT 2B receptors are slightly expressed in neurons located in the cerebellum, the posterior hypothalamus, the lateral septum and the medial amygdala but these data, which are derived from immunohistochemical staining (IHS) (20), are considered controversial. Other studies using IHS and molecular biological methods showed expression in motoneurons (21), in rat spinal cord and in dorsal root ganglion (DRG) (22)(23)(24). The subcellular localization of the receptor in blood vessels is not evident from the literature; however, it has been suggested that it is localized on the luminal side of vascular endothelial cells (11).…”
Section: Structure and Localization Of 5-ht 2b Receptorsmentioning
confidence: 99%